2007
DOI: 10.2224/sbp.2007.35.7.903
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Correlation Between Depression and Hopelessness Levels in Mothers of Disabled Children

Abstract: This research was conducted to examine the correlation between depression and hopelessness levels in mothers of disabled children between the ages 5 and 7. A total of 126 mothers of children with disabilities was used in the study. They were obtained from the nursery schools of the First Education Schools of the Ministry of Education or from private schools. In this study the Beck Depression Scale (Beck, Ward, Mendelson, Mock, & Erbaugh, 1961), Beck Hopelessness Scale (Beck, Lester, & Trexler, 1974) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…When a child is born with a disability, the mother is often blamed and belittled by society, and false explanations may be attributed to her child's disability, leading to her feeling hopeless about the future (1). Mothers, more so than fathers, are at higher risk of depression because they tend to take active roles in caring for their children with disabilities, even relinquishing their jobs or leisure activities (6).…”
Section: The Impact Of Children With Disabilities On Parental Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…When a child is born with a disability, the mother is often blamed and belittled by society, and false explanations may be attributed to her child's disability, leading to her feeling hopeless about the future (1). Mothers, more so than fathers, are at higher risk of depression because they tend to take active roles in caring for their children with disabilities, even relinquishing their jobs or leisure activities (6).…”
Section: The Impact Of Children With Disabilities On Parental Wellbeingmentioning
confidence: 99%
“…The birth of a child with a disability has adverse consequences for the lives, emotions, and behaviours of all family members. These consequences arise because looking after a child with a disability is very difficult and families are not prepared for it (1). Families with children with disabilities experience very high levels of stress and depression (2–4).…”
mentioning
confidence: 99%
“…), more symptoms of stress, depression, anxiety, hopelessness and somatic complaints (Uğuz et al . , Ceylan & Aral , Fen Gau et al . ) and more need for social support than fathers (Helitzer et al .…”
Section: Introductionmentioning
confidence: 99%
“…A Turkish study by Sen and Yurtsever () revealed that 90% of the family members of intellectually disabled children wanted to receive support from nurses. In spite of many descriptive studies revealing the problems encountered by the families of intellectually disabled children in Turkey (Ceylan & Aral , Bumin et al . , Dereli & Okur , Coşkun & Akkaş , Karadağ , Keskin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Continuity of these problems brings depression and hopelessness as a part of their lives for the parents with children with disabilities. Thus, various studies conducted on parents with handicapped children revealed that the difficulty of dealing with their children caused them experience depression (Bahar, Bahar, Savaş & Parlar, 2009;Bitsika & Sharpley, 2004;Blacher, Lopez, Shapiro & Fusco, 2016;Ceylan & Aral, 2007a;Foster, Garber & Durlak, 2008;Karadağ, 2009) and hpelessness (Ceylan & Aral, 2007b;Ergüner-Tekinalp & Akkök, 2004;Karadağ, 2009;Zembat & Yıldız, 2010) in their lives. In conclusion, since being disabled or with special needs is a long-lasting situation, it becomes inevitable for parents to live depression and hopelessness.…”
Section: Introductionmentioning
confidence: 99%